Characterization of indole-3-acetic acid-producing marine yeasts and their effect on tomato (Solanum lycopersicum L.) seedlings - Kaewkrajay, Chutima; Kotabar, Tuankumari; Dethoupb , Tida (Agriculture and Natural Resources, 2025)
Importance of the work: The marine yeasts Rhodotorula mucilaginosa DMKU 7233-1 and Papiliotrema laurentii DMKUFC10-4 had strong potential for producing indole-3-acetic acid (IAA). Their cell suspension promoted tomato seed germination and increased stem size. Objectives: To screen IAA-producing yeasts, analyze their phytobeneficial attributes, evaluate their antagonistic activity against Agroathelia rolfsii, to study low-cost substrates suitable for IAA production and to evaluate the effectiveness of yeast cells on tomato seed germination. Materials and Methods: In total, 49 marine yeasts were screened for IAA production. Phytobeneficial attributes (nutrient solubilization, production of cell wall-degrading enzymes and synthesis of active substances) were evaluated. The antagonistic activity was studied between the yeasts and A. rolfsii. Low-cost carbon sources for IAA production were investigated and tomato seed bioassays were conducted. Results: The marine yeasts R. mucilaginosa DMKU 7233-1 and P. laurentii DMKUFC10-4 produced the best results for IAA production. Although neither strain could solubilize phosphate or zinc oxide, and they did not produce siderophores or NH3, both strains were able to produce catalase and cellulase. There was no antagonistic activity between either of the yeast strains and A. rolfsii. IAA production in sugarcane molasses medium amended with 0.1% L-tryptophan (L-trp) yielded the best results at 1,379.4 ± 29.6 mg/L with DMKU 7233-1 and 681.4 ± 38.8 mg/L with DMKUFC10-4. Tomato seedlings treated with P. laurentii DMKUFC10-4 had a high germination rate (100%), while R. mucilaginosa DMKU 7233-1 produced the best outcome based on enhancement of stem size. Main finding: The yeast strains DMKU 7233-1 and DMKUFC10-4 were effective at producing IAA in a medium amended with 0.1% L-trp. Sugarcane molasses was a suitable carbon source. Cell suspension of both yeast strains promoted the growth of tomato seedlings.